1994
DOI: 10.1136/vr.134.3.60
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Streptococcus suis serotype 2 and porcine reproductive and respiratory syndrome virus in specific pathogen-free piglets

Abstract: Secondary specific pathogen-free (sSPF) piglets were inoculated intranasally with Streptococcus suis serotype 2 alone, porcine reproductive and respiratory syndrome virus (PRRSV) alone, or with PRRSV followed by S suis. Uninfected piglets were used as controls. Pigs inoculated with PRRSV (ATCC VR-2332) followed by challenge with a virulent strain (87555) of S suis serotype 2 developed clinical signs, suppurative meningitis and large numbers of S suis in their tissues, including the brain and meninges. Pigs ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
0
8

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(116 citation statements)
references
References 0 publications
1
107
0
8
Order By: Relevance
“…The severity of experimentally reproduced clinical signs and lesions with PRRS virus alone were generally mild to moderate [4]. It has been demonstrated that concurrent infection with PRRS virus and porcine respiratory coronavirus infection or swine influenza virus [17], or PRRS virus and Streptococcus suis [3] can induce more severe disease than that with PRRS virus alone. It is possible to speculate that at least during period of virus infection in AM, the defense in the lung is suppressed and the susceptibility of an infected animal to secondary bacterial or virus infection is increased.…”
Section: Resultsmentioning
confidence: 99%
“…The severity of experimentally reproduced clinical signs and lesions with PRRS virus alone were generally mild to moderate [4]. It has been demonstrated that concurrent infection with PRRS virus and porcine respiratory coronavirus infection or swine influenza virus [17], or PRRS virus and Streptococcus suis [3] can induce more severe disease than that with PRRS virus alone. It is possible to speculate that at least during period of virus infection in AM, the defense in the lung is suppressed and the susceptibility of an infected animal to secondary bacterial or virus infection is increased.…”
Section: Resultsmentioning
confidence: 99%
“…Kay et al [37] described an episode of chronic respiratory disease, in a herd in the UK, in which PRRSV and SIV co-infection was detected. Bacterial agents are also implicated as potential synergists in field studies of the respiratory form of PRRS [28,49]. A retrospective analysis by Zeman [72] identified concurrent pulmonary bacterial infections in 58% of 221 PRRS cases, most commonly being Pasteurella multocida, Streptococcus suis, Haemophilus parasuis and Salmonella spp., with SIV only rarely being implicated.…”
Section: Field Observations Of Immunomodulationmentioning
confidence: 99%
“…Cooper et al [21] were unable to potentiate infections by challenge of 4-5 week-old specific pathogen-free (SPF) pigs with H. parasuis, S. suis, S. cholerasuis or P. multocida seven days after infection with an American PRRSV strain (AmPRRSV). But Galina et al [28], using the virulent strain of S. suis serotype 2 (DH5) in SPF piglets, observed that only those which had previously been inoculated with EuPRRSV developed clinical signs, a suppurative meningitis and large numbers of the bacteria in tissues, including the brain and meninges. The authors later postulated that the observed interaction of PRRSV with S. suis was not through the destruction of macrophages, but rather that PRRSV inflames and destroys the nasal mucosa, resulting in phagocyte infiltration and uptake of S. suis to the brain [49].…”
Section: Experimental Investigations Of An Immunomodulation Theorymentioning
confidence: 99%
“…Los experimentos tendientes a determinar el rol predisponente de las cepas del virus de baja virulencia a infecciones secundarias bacterianas o virales han demostrado que estas cepas predisponen a infecciones secundarias por bacterias como el Streptococcus suis (Galina et al, 1994 ). Por otro lado, infecciones mixtas del VPRRS con otros virus respiratorios, como el coronavirus respiratorio, han resultado en una enfermedad respiratoria mĂĄs severa (Van Reeth et al, 1996).…”
Section: Discussionunclassified